Direct and Gradual Electrical Testicular Shocks Stimulate Spermatogenesis and Activate Sperms in Infertile Men: A Randomized Controlled Trial - Hashim Talib Hashim; Joseph Varney; Zanyar Qais; Abdallah Reda; Shohra Qaderi; Nazmus Sakib Chowdhury; Kimberly Murry; Jaffer Shah; Adil Alhaideri; Shoaib Ahmad; Ali Talib Hashim; Rehana Rehman; et al. (American Journal of Men's Health)
Infertility was reported in approximately 15% of all heterozygous couples, with the male factor accounting for nearly half of the cases. This typically occurs due to low sperm production, sperm dysfunction, and sperm delivery obstruction. In this randomized controlled single-blind clinical trial, 90 infertile male subjects diagnosed with oligospermia, hypospermia, asthenozoospermia, or necrozoospermia were recruited. Semen samples were obtained with the masturbation method and an assessment of semen volume, sperm count, and motility was performed. Five milliamps of electrical shock was delivered to the participants through the fertility improvement device. Semen analysis was collected 4 months post-intervention from all subjects. Data were collected and an analysis of pre- and post-intervention results was performed. There was an improvement in the count, volume, and motility of the patient’s sperm after electrical shock treatment compared with the control group. By using the analysis of variance (ANOVA) test, there were statistically significant differences between the first and the second seminal analysis results (<.05). All other results were found to be independently correlated. This study demonstrated that using a painless, convenient at-home device, which is designed to contain all the testis tissue as a cup and then extend to include the scrotal roots reaching the penile root to include the epididymis, could significantly improve sperm motility and count. This device can be utilized to tackle the significant issue of infertility in a cost-effective, safe, and efficacious manner. An ultrasound was done before and after using the device as well as years after with no changes noted. Clinical Trial’s Registration Number: NCT04173052